Pediatric regenerative endodontics - Mukesh Kumar Hasija; Babita Meena; Deepti Wadhwa; Dipanshu Kumar (Wolters Kluwer Medknow Publications, 2021)
The vitality of dentin-pulp complex is fundamental to the life of the tooth and is a priority for targeting clinical management strategies. One novel approach to restore tooth structure is based on biology: regenerative endodontic procedure by application of tissue engineering. Regenerative endodontics is an exciting new concept that seeks to apply the advances in tissue engineering to the regeneration of the pulp-dentin complex. The basic logic behind this approach is that patient-specific tissue-derived cell populations can be used to functionally replace integral tooth tissues. The development of such "test tube teeth" requires precise regulation of the regenerative events to achieve proper tooth size and shape, as well as the development of new technologies to facilitate these processes. This article provides a general review of literature and a case report on the concept of revascularisation and its application in endodontics, providing an insight into the new developmental approaches on the horizon.